Validation and Clinical Utility of ELISA Methods for Quantification of Amyloid-β of Peptides in Cerebrospinal Fluid Specimens from Alzheimer’s Disease Studies - Lachno, D Richard; Evert, Barbara A; Maloney, Kaia; Willis, Brian A; Talbot, Jayne A; Vandijck, Manu; Dean, Robert A (Journal of Alzheimer's disease, 2015)
The aim of this study was to validate assays for measurement of amyloid-β (Aβ) peptides in cerebrospinal fluid (CSF)specimens according to regulatory guidance and demonstrate their utility with measurements in specimens from Alzheimer’s disease (AD) studies. Methods based on INNOTEST(®)β-AMYLOID(1-42) and prototype INNOTEST(®)β-AMYLOID(1-40) ELISAkits were developed involving pre-analytical sample treatment with Tween-20 for reliable analyte recovery.Validation parameters were evaluated by repeated testing of CSF pools collected and stored in the same manner as clinical specimens. Intra- and interassay coefficients of variation were ≤11% and relative accuracy was within ± 10% for both analytes. Dilutional linearity was demonstrated for both analytes from a spiked CSF pool, but not from a non-spiked native CSF pool. Recovery of standard Aβ peptide spikes standard ranged from 77% to 93%. No interference was observed from the investigational drugs LY2811376, LY2886721, LY3002813, or semagacestat. Aβ(1-40) and Aβ(1-42) were stable in CSF for up to 8 hours at room temperature and during 5 f reeze-thaw cycles from ≤−20◦C and ≤−70◦C. In frozen native CSF specimens, Aβ(1-40) was mostly stable up to 3 years at ≤−70◦C, whereas stability of Aβ(1-42) was limited to 221 days. Dose-dependent changes in measured CSF Aβ were observed in healthy volunteers up to 36 hours after treatment with the-site cleavage enzyme inhibitor LY2886721. In conclusion, rigorous validation tests have successfully demonstrated the strengths and operational limitations of these INNOTEST(®)-based assays.They have proved to be robust and reliable tools for pharmacodynamic evaluations of investigational AD therapeutics in clinical trials.